THE USE OF ILLUSTRATIVE MEANS IN ISLAMIC HISTORY ARTISTIC WORKS (XVIIIXIX CENTURIES) (Western European Journal of Historical Events and Social Science, 2025)
The article analyzes the artistic means of depiction of stories that artistically express Islamic history in Uzbek classical literature in the 18th-19th centuries. The issues of artistic analysis are illustrated using the examples of the works of Jahon Atin Uvaisiy, Kholis Toshqandiy, and Abdukayum Wahmiy, and general conclusions are drawn on their specific features.